2018
DOI: 10.1590/0034-761220170020
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of CCTs from Latin America to Asia: the Philippine 4Ps case

Abstract: The purpose of this study is to understand the role of international and domestic actors, ideas and processes in the diffusion of public policies. It argues that existing studies on the subject do not provide an adequate explanation of the mechanisms through which diffusion takes place, nor do they sufficiently address the roles of actors affecting the policy transfer process. We address these shortcomings by studying the diffusion of conditional cash transfer (CCT) programs from Brazil and Mexico to the Phili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
13
0
2
Order By: Relevance
“…Instrument constituencies actively develop comprehensive knowledge about specific policy instruments and advocate for its adoption. Cases of instrument constituencies include emissions trading schemes (Voß & Simons, ), experimental sustainability management (Voß, ), public participation (Amelung & Grabner, ; Voß & Amelung, ) and social policies (Béland & Howlett, ) including conditional cash transfers (Foli, Béland, & Fenwick, ; Howlett, Ramesh, & Saguin, ). They are found to mobilize resources with the intention of deploying these tools in developing and developed countries alike, regardless of policy context.…”
Section: Instrument Constituency and Its Role In Policy Transfermentioning
confidence: 99%
See 4 more Smart Citations
“…Instrument constituencies actively develop comprehensive knowledge about specific policy instruments and advocate for its adoption. Cases of instrument constituencies include emissions trading schemes (Voß & Simons, ), experimental sustainability management (Voß, ), public participation (Amelung & Grabner, ; Voß & Amelung, ) and social policies (Béland & Howlett, ) including conditional cash transfers (Foli, Béland, & Fenwick, ; Howlett, Ramesh, & Saguin, ). They are found to mobilize resources with the intention of deploying these tools in developing and developed countries alike, regardless of policy context.…”
Section: Instrument Constituency and Its Role In Policy Transfermentioning
confidence: 99%
“…The idea of social development remains the same but other elements became a by‐product of local contestations. Howlett et al () used the three categories of policy elements identified by Cashore and Howlett () to show the influence of instrument constituency on the journey of CCT from Latin America to the Philippines. The authors argued that the fundamental ideas (or high‐level abstraction) about goals and instrument logic emanated from United States and Chile but the program‐level content on specific policy objectives and instrument mechanism became a concoction of various practices from Latin America including Brazil and Mexico.…”
Section: Instrument Constituency and Its Role In Policy Transfermentioning
confidence: 99%
See 3 more Smart Citations